2016
DOI: 10.1007/s00595-016-1414-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the necessity for chest drain placement following thoracoscopic wedge resection

Abstract: PurposeTo evaluate the outcomes of patients who underwent thoracoscopic wedge resection without chest drain placement.MethodsThe subjects of this retrospective study were 89 patients, who underwent thoracoscopic wedge resection at our hospital between January, 2013 and July, 2015. A total of 45 patients whose underlying condition did not meet the following criteria were assigned to the “chest drain placement group” (group A): peripheral lesions, healthy lung parenchyma, no intraoperative air leaks, hemorrhage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 12 publications
0
35
0
1
Order By: Relevance
“…Existen pocos reportes de realizar un procedimiento abierto sin colocación de drenaje torácico en resecciones lingulares. 16 Común-mente las publicaciones de resección en cuña e incluso lobectomías sin tubo torácico sin complicaciones severas se refieren a los realizados por videotoracoscopia, con las ventajas de menos dolor, pequeñas incisiones y menor trauma, 17,18 y su uso innecesario incrementa la estadía hospitalaria sin reducción de la incidencia de neumotórax. 19 Del total de biopsias pulmonares por minitoracotomía, decidimos no dejar drenaje pleural en aquellos pacientes que cumplieran los siguientes criterios: a) pulmones de consistencia blanda, b) expansibilidad adecuada, c) adherencias pleuropulmonares laxas o inexistentes, d) sin engrosamiento pleural, e) no fugas aéreas observadas a maniobras de Valsalva mientras se vierte agua en la línea de sutura y f) ausencia de derrame pleural.…”
Section: Discussionunclassified
“…Existen pocos reportes de realizar un procedimiento abierto sin colocación de drenaje torácico en resecciones lingulares. 16 Común-mente las publicaciones de resección en cuña e incluso lobectomías sin tubo torácico sin complicaciones severas se refieren a los realizados por videotoracoscopia, con las ventajas de menos dolor, pequeñas incisiones y menor trauma, 17,18 y su uso innecesario incrementa la estadía hospitalaria sin reducción de la incidencia de neumotórax. 19 Del total de biopsias pulmonares por minitoracotomía, decidimos no dejar drenaje pleural en aquellos pacientes que cumplieran los siguientes criterios: a) pulmones de consistencia blanda, b) expansibilidad adecuada, c) adherencias pleuropulmonares laxas o inexistentes, d) sin engrosamiento pleural, e) no fugas aéreas observadas a maniobras de Valsalva mientras se vierte agua en la línea de sutura y f) ausencia de derrame pleural.…”
Section: Discussionunclassified
“…A number of clinical trials have been conducted to explore the feasibility and safety of omitting chest tube after pulmonary surgery, and found that NCT after pulmonary does not increase the morbidity and mortality, and meanwhile decrease the pain scale postoperatively. Some institutions have made efforts to explore the benefits of NCT especially for small pulmonary nodules underwent VATS wedge (5)(6)(7)9,10,24). At the same time, a few studies set out to explore the feasibility of NCT for patients experiencing VATS major lung resection (8,11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic surgeons have tried amounts of methods to reduce postoperative pain and have achieved much progress such as reducing the number of chest tubes, using more flexible and slender chest tubes (21,26,27). Five of the nine included studies reported postoperative pain scale measured in the VAS (6,8,10,11,13) and three study reported the dosage of antalgesic (5,9,13). Patients in the NCT group have lighter pain in POD1 and used less antalgesic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest tubes, a ubiquitous presence on a thoracic surgery service, can be associated with significant neuralgia, tubing and connection-related issues, and iatrogenic pneumothorax at time of removal. A recent report by Lu and colleagues 9 documented a series of 44 patients in whom chest tubes were omitted after wedge resection. To select a low-risk group, only patients with peripheral lesions, healthy lung parenchyma, no intraoperative air leaks, hemorrhage or effusion accumulation, and no pleural adhesion were included.…”
mentioning
confidence: 99%